Reclaiming Integrity in the Post-Truth Era: Reconstructing Pastoral Leadership Based on Ephesians 4:15 - Yohanes Twintarto Agus Indratno; Edi Zakarijah (Sekolah Tinggi Teologi Transformasi Indonesia, 2026)
The post-truth era presents a crisis of truth and integrity that clearly affects Christian leadership practices, particularly regarding the integrity and morality of pastors. The relativization of truth often shifts the theological foundations of church ministry, thereby risking the loss of pastoral leadership's integrity. Even the phenomenon of digital disinformation and the erosion of leadership morality in this era underscores the urgency of reconstructing a leadership model grounded in biblical texts. This study aims to conduct an exegetical analysis of Ephesians 4:15 as a theological foundation for pastoral leadership integrity in a post-truth culture. The method employed is exegetical analysis using a grammatical-historical and theological-syntactic approach. The results of the study show that Ephesians 4:15 emphasizes the integration of truth and love as the foundation for the church’s growth toward Christ as its Head. This theological dimension affirms pastoral leadership that is character-based, integrity-based, and Christ-centered amid the challenges of the post-truth culture. Thus, the pastoral leadership paradigm built from this text is able to guide the congregation to live according to the values of God’s truth.